Association of serum 25-hydroxyvitamin D levels with age-related macular degeneration and its clinical correlates: a cross-sectional study - Liang, Xu; Wang, Jiaxing; Zhang, Yue; Zheng, Hui (Frontiers in Endocrinology, 2025)
IntroductionAge-related macular degeneration (AMD) is a leading cause of irreversible vision loss in older adults, with significant inter-individual variability in clinical progression. Vitamin D, known for its role in calcium homeostasis and anti-inflammatory pathways, may be implicated in AMD pathogenesis. This study aimed to investigate serum 25-hydroxyvitamin D [25(OH)D] levels in AMD patients and their association with clinical phenotypes.MethodsThis single-center, cross-sectional observational study was conducted at Tianjin Eye Hospital, China, involving 210 participants (100 AMD patients and 110 healthy controls). Exclusion criteria included conditions affecting vitamin D metabolism and recent vitamin D supplementation. Comprehensive ophthalmic assessments and laboratory tests were performed. Data were analyzed using R software, employing Student’s t-tests, ANONA, chi-squared tests, Pearson correlation and linear regression models.ResultsAMD patients exhibited significantly lower serum 25(OH)D levels than controls (22.98 ± 7.30 ng/mL vs. 26.12 ± 9.81 ng/mL, p=0.013). Within the AMD group, late-stage patients had lower 25(OH)D levels than early-stage patients (22.53 ± 8.14 ng/mL vs. 23.46 ± 6.36 ng/mL, p=0.019) and higher CRP levels (0.31 ± 0.19 mg/L vs. 0.17 ± 0.05 mg/L, p=0.015). ROC curve analysis indicated moderate diagnostic utility of 25(OH)D for distinguishing AMD patients from controls (AUC=0.714, 95% CI: 0.58-0.73, p<0.01), but limited ability to differentiate early vs. late-stage AMD Linear regression analysis revealed positive associations between 25(OH)D levels and apolipoprotein E (ApoE, β=0.157, p=0.04) and serum creatinine (β=0.18, p=0.02).ConclusionThis study provides evidence linking lower serum 25(OH)D levels to the presence and severity of AMD, particularly in late-stage disease.